Efektifitas Pemberian Intervensi Minyak Zaitun Pada Risiko Luka Tekan Di Ruang ICU RSUP DR. Wahidin Sudirohusodo Makassar : Studi Kasus - Eva Yustilawati; Ilhamsyah Ilhamsyah; Ardian Adiwijaya; Muh. Reza Irsandi Putra B (Alauddin Scientific Journal of Nursing, 2023)
Chronic Kidney Disease (CKD) or chronic kidney disease refers to the progressive and irreversible abnormal function of the kidneys, resulting in the body's inability to maintain a balance of metabolism, fluid, and electrolytes effectively. The purpose of this case study was to determine the effectiveness of olive oil administration at Dr. Wahidin Sudirohusodo Makassar Teaching Hospital. The method used in this study was a case study approach, collecting data through observation, interviews, physical evaluation, and documentation, on one patient as a sample. The data analysis results showed that olive oil administration for 3 days indicated a decrease in the risk of pressure ulcers. This intervention was given once a day by applying olive oil to the patient's back, and the monitoring results before and after the intervention showed decubitus scores on day 1 (13-13), day 2 (13-11), and day 3 (11-11). There was a decrease in the decubitus scores, although not significant, as the patient was in a sedated condition with a total dependence level. The conclusion of this case study is that olive oil can prevent the occurrence of pressure ulcers with a decrease in decubitus scores over 3 days. The recommendation from the research results is that olive oil intervention can be a patented non-pharmacological therapy for long-term patient care with minimal impact, easy accessibility, and economical.